The Dynamics of the Anti-Shia Movement: An Analysis of International and National Geopolitics - Makhsum, Ali; Wafi, Mahmud Hibatul (Contemporary Society and Politics Journal, 2024)
This study aims to analyze the dynamics of the anti-Shia movement within the context of international and national geopolitics, emphasizing how sectarian issues are exploited as tools for political, ideological, and power mobilization. The research is based on the premise that the anti-Shia movement is not merely a theological conflict but also encompasses geopolitical dimensions that affect international relations and domestic stability in Indonesia. The study employs a qualitative method with a descriptive-analytical approach. Data collection was conducted through literature studies, media analysis, and reviews of relevant documents from both primary and secondary sources. Social movement analysis was applied to understand the mobilization strategies of anti-Shia groups, while a geopolitical approach was used to evaluate the influence of international relations on the emergence of this movement in Indonesia. Furthermore, content analysis of publications in print, digital, and social media was conducted to explore the narratives and communication strategies of anti-Shia groups. The findings reveal that the anti-Shia movement is closely tied to the geopolitical dynamics of the Middle East, particularly the conflict between Sunni and Shia forces supported by state actors such as Saudi Arabia and Iran. In Indonesia, this issue has been adopted by certain groups as a political tool to bolster the dominance of specific ideologies, often leveraging religious sentiments. The study also found that media plays a critical role in amplifying anti-Shia narratives, thereby creating societal polarization. These findings underline that the anti-Shia movement cannot be understood in isolation but must be examined as part of a broader and more complex geopolitical dynamic.